Distribution of mental health diagnoses in relation to sexual orientation and gender discontent in a late adolescent community population - Gerdner, Arne; Skoog, Therése; Kapetanovic, Sabina; Claesdotter-Knutsson, Emma; Askelöf, Susanna ; 0009-0000-1952-0901; Håkansson, Anders ; 0000-0002-5800-8975 (BMC Psychiatry, 2025)
BACKGROUND: Few population studies have assessed the prevalence of various psychiatric disorders separately for sexual and gender minority groups, and none in an adolescent population. Given the increased mental health problems in sexual and gender minority groups combined, the present study aimed to estimate prevalence of mental disorders in separate sexual minority groups as well as gender discontent persons in community-recruited adolescents in Sweden. METHODS: The present study is based on two waves (at 17 and 18 years of age) of a longitudinal cohort study (N = 949; 56% with female and 44% male legal gender, of which 1.7% reported gender discontent). Diagnostic data of 20 mental health disorders (psychiatric, substance use, and addictive behavior disorders) for each group of sexual orientation (asexual, homosexual, bisexual, and heterosexual) and gender discontent are reported, based on structured screening and subsequent diagnostic procedures. RESULTS: The largest prevalence of mental health disorders was detected in homosexual girls and in bisexuals of both genders. Among asexual individuals, and among homosexual boys, none of the participants fulfilled the mental health disorders assessed. Gender discontent was associated with a moderately higher number of mental health disorders. CONCLUSION: Mental health services, both in specialized psychiatry and in community-based services targeting the mental health of adolescents may need to take into consideration the increased vulnerability for mental health disorders in bisexual individuals and in female homosexual individuals. Further research with larger samples is essential to better understand mental health in asexual individuals, young male homosexuals, and transgender or gender discontent populations.
© 2025. The Author(s).
Keywords: Humans; Adolescent; Male; Female; Mental Disorders/epidemiology; Sweden/epidemiology; Longitudinal Studies; Sexual and Gender Minorities/psychology; Prevalence; Sexual Behavior/psychology